Educational intervention on knowledge about depression among secondary level students of Gokarneshwor municipality, Kathmandu. - Limbu,Dipesh (2017)
ABSTRACT: The main purpose of this research is to evaluate the change in students ' Knowledge about depression after providing educational intervention. The area of the study was Gokarneshwor Municipality. The source of data collection was primary source from self administered questionnaire. Altogether there was 227 respondent in both intervening and control group in this study. The study design was pre-test and post-test with control group. The data were entered and analyzed in SPSS where both qualitative and quantitative data were collected, Schools were selected randomly and were assigned as intervention group and control group. Students were provided with self administered questionnaire and were asked to give answer that they felt was correct. After evaluating their response from pre-test intervening groups were provided with educational intervention 3 days and each session was of 2 hours long with the use of all the possible resources such as power-point presentation charts, and audio-visual. After a week of providing intervention post-test data collection was conducted . No any intervention was given to the control groups. In intervening groups, 51.1% were male and 48.9% were female whereas in control group 54.2% were male and 43.2% were female. Prior the study 93.8% in control group had heard about depression. Around 38.8% defined depression as stress/tension/frustration after invention. Before intervention 76.7% of respondent disagreed that some people are immune to depression where as 94.7% disagreed after intervention. Similarly,70.9% of control group disagreed that some people are immune to depression 69.6% disagreed during post-test. About 97.4% of respondent said that they will seek help for their friends/family if they are depressed before intervention whereas after intervention 100% said that they will help. Likewise, I control group 97.4% and 95.6% said they will help during pre-test and post-test respectively. In order to evaluate the effectiveness of educational intervention paired t test was carried out using SPSS . There was significant difference between pre-test and post -test results and P value was 0.000 which was less than 0.05 hence the conclusion was drawn that educational intervention was effective. Similarly, p value of control was found to be 0883 which was higher than 0.05 hence, there was no significant difference between pre-test and post-test in control group.